Transmission/reflection behaviors of surface plasmons at an interface between two plasmonic systems. (22nd February 2018) - Guan, Fuxin; Sun, Shulin; Ma, Shaojie; Fang, Zhening; Zhu, Baocheng; Li, Xin; He, Qiong; Xiao, Shiyi; Zhou, Lei
Abstract: Although surface plasmon polaritons (SPPs) have been intensively studied in past years, the transmission/reflection properties of SPPs at an interface between two plasmonic media are still not fully understood. In this article, we employ a mode expansion method (MEM) to systematically study such a problem based on a model system jointing two superlattices, each consisting of a periodic stacking of dielectric and plasmonic slabs with different material properties. Such a generic model can represent two widely used plasmonic structures (i.e. interfaces between two single dielectric/metal systems or between two metal–insulator–metal waveguides) under certain conditions. Our MEM calculations, in excellent agreement with full-wave simulations, uncover the rich physics behind the SPP reflections at generic plasmonic interfaces. In particular, we successfully derive from the MEM several analytical formulas that can quantitatively describe the SPP reflections at different plasmonic interfaces, and show that our formulas exhibit wider applicable regions than previously proposed empirical ones.